2001
DOI: 10.1002/med.1010
|View full text |Cite
|
Sign up to set email alerts
|

Arterial calcification: A review of mechanisms, animal models, and the prospects for therapy

Abstract: The causes of arterial calcification are beginning to be elucidated. Macrophages, mast cells, and smooth muscle cells are the primary cells implicated in this process. The roles of a variety of bone-related proteins including bone morphogenetic protein-2 (BMP-2), matrix Gla protein (MGP), osteoprotegerin (OPG), osteopontin, and osteonectin in regulating arterial calcification are reviewed. Animals lacking MGP, OPG, smad6, carbonic anhydrase isoenzyme II, fibrillin-1, and klotho gene product develop varying ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(47 citation statements)
references
References 223 publications
2
40
0
3
Order By: Relevance
“…20,56 LPC induces apoptosis in a variety of cell types. When LPC was applied to rat pancreatic AR42J cells, there was an increase in DNA fragmentation as concentrations of LPC increased up to 25 μM.…”
Section: Discussionmentioning
confidence: 99%
“…20,56 LPC induces apoptosis in a variety of cell types. When LPC was applied to rat pancreatic AR42J cells, there was an increase in DNA fragmentation as concentrations of LPC increased up to 25 μM.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that genetic variations in the OPG gene may play a role in the pathophysiology of this disease. Since several currently available drugs have been shown to retard the rate of arterial calcification, e. g. hormone replacement therapy, selective estrogen receptor modulators, statins and calcium channel blockers [45], these findings may be informative for the primary prevention of this disease. Whether early pharmacological intervention, aimed at reducing vessel wall mineralization in this genetic subpopulation, is warranted for the prevention of ICH, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…58 Similarly, osteogenic reprogramming is well described in vascular (particularly medial) calcification. 59,60 Bone morphogenetic protein 2 (BMP-2)-dependent signalling has been shown to lead to activation of osteoblast-associated transcription factors and the resultant increased expression of osteogenic proteins. 6163 Using advanced material-based analytical methods, investigators identified spherical particles containing calcium phosphate mineral in calcified aortic valves and calcific regions of the vessel wall.…”
Section: Pathophysiologymentioning
confidence: 99%